Investigating Innovative Activities for Teaching Arabic in Secondary School - Rini Astuti; Husnul Fatarib; Rodhy Harisca; M. Kholis Amrullah; Nada Ghneim (The Arabic Education Department Postgraduate Programs, UIN Sultan Maulana Hasanuddin Banten in Partnership with PPJKBA Indonesia, 2023)
Language activities are part of the linguistic environment as means of teaching Arabic. As for the linguistic environment, it has an important role in the acquisition of language by linguistic activities in it. This language activity program in an innovative way is a solution for educational institutions that have difficulty in making students able to achieve four language skills and stimulate students to think flexibly, fluently and innovatively. The approach used in this research is the qualitative approach. The results of this research are the things that need attention and improvement in the implementation of innovative language activities, which are the innovation of the teacher, the innovation of the teacher is the main requirement in the development of students' motivation and innovation. The innovative teacher will provide innovative inspiration to students with different stimuli to train students' innovation. If the teacher is good at motivating students to study seriously. Students who are already motivated, will develop their innovation during the classroom learning process. Teacher innovation is required during the education process. Innovative education will make students more attention and ability to better develop their material.